ROLE OF MANAGEMENT OF THE BRAND AND INCREASING THE COMPETITIVENESS OF ENTERPRISES (Euro-Asia Conferences, 2021)
In the state of practical recommendations for the creation of aneffective system of brand management, the role of brand management and theimportance of brand management in increasing the competitiveness ofenterprises.